A trajetória escolar pregressa de alunos com deficiência intelectual matriculados na Educação de Jovens e Adultos (EJA) - Lebrão, Olga Maria Freitas de Oliveira Falleiros (2019)
The objective of this research was to identify and analyze the previous trajectory of students with intellectual disabilities enrolled in Youth and Adult Education (EJA) of Rede Municipal de São Paulo, in the year 2017, in view of the growth, in recent years, of the student's enrollment in this type of education. The data of these trajectories were obtained through the Microdados of the Census of Basic Education made available by the Instituto Nacional de Pesquisas Educacionais Anísio Teixeira (MEC/INEP), from 2007 to 2016, since this database, although existing since 1995, does not allow data to be collected on school trajectories prior to 2007. For this reason, the age range of 15 to 22 years was limited, as older students could have completed their previous trajectories in years prior to 2007. Although the PMSP offers five distinct types of EJA, were selected students who were enrolled in the courses offered by Municipal Schools of Elementary Education (EMEFs) because they are the ones with the most qualified structure. This procedure resulted in the selection of 160 (one hundred and sixty) students, whose trajectories were analyzed by the following indicators: age, sex, race/color, EJA’s teaching stage, type of trajectory, school progression, number of retentions, years of enrollment registered, previous series to the EJA achieved and type of schooling. The main findings were: the concentration of students under 19 years old, the low incidence of female students, and the corresponding number of blacks and whites. With regard to the previous trajectories, it was verified that the majority had studied a good part of the fundamental education, with a constant trajectory and regular progression, which shows that, although they had formally studied a great part of elementary school, they had not assimilated the content school